Influence of the magnetic field on microorganisms in the oral cavity - BRKOVIC, Snezana; POSTIC, Srdjan; ILIC, Dragan (Journal of Applied Oral Science, 2015)
Since the beginning of their lives, all living organisms are exposed to the influence of geomagnetic fields. Objectives : With respect to the positive effects that magnetic fields have on human tissues, especially the bactericidal effect, this investigation aimed to assess their influence on the reduction of oral microorganisms. Material and Methods : In order to obtain adequate specimens of dental plaque deposit, microbes such as Streptococcus parasanguinis, Staphylococcus epidermidis, Rhodococcus equi and Candida albicans were isolated from the human mouth. To establish the intensity of microbial growth on the basis of the modified optical density (OD) of agar turbidimetry assay, microbial count and spectrophotometry were applied. The study was carried out with two microbial concentrations (1 and 10 CFU/ml) after periods of incubation of 24 and 48 h and using micromagnets. Results : A positive effect of the magnetic field, resulting in the reduction of dental plaque microbes in vitro, was found. In the first 24 hours of exposure to the magnetic field, the number of all isolated microbes was significantly reduced. The most potent influence of magnets and the most intensified reduction after 24 hours were evident in Candida albicans colonies. The decrease in the influence of magnets on microbes in vitro was also detected. Conclusions : Magnets reduce the number of microbes and might be recommended as a supplement in therapy for reduced periodontal tissues. This is important because periodontal tissues that are in good conditions provide prolonged support to the oral tissues under partial and supradental denture.